Arboviruses and blood meal sources in zoophilic mosquitoes at human-wildlife interfaces in Kenya - Musa, A.A.; Muturi, M.W.; Musyoki, A.M.; Ouso, D.O.; Oundo, J.W.; Makhulu, E.E.; Wambua, Lillian; Villinger, J.; Jeneby, M.M. (Mary Ann Liebert Inc, 2020)
Background: Zoophilic mosquitoes play an important role in the transmission of arboviruses of medical importance at human-wildlife interfaces, yet arbovirus surveillance efforts have been focused mostly on anthropophilic mosquitoes. Understanding the diversity of zoophilic mosquitoes and their associated feeding patterns and arboviruses can inform better vector control strategies. Materials and Methods: We morphologically identified mosquitoes collected from two game reserves in Kenya, the Maasai Mara National Reserve (MMNR) and locations near the Shimba Hills National Reserve (SHNR). Representative mosquitoes were also identified by cytochrome c oxidase subunit 1 (COI) barcode sequencing. In addition, we identified the vertebrate hosts of mosquito blood meals from the contents of each mosquito's abdomen by high-resolution melting (HRM) analysis and sequencing of COI, 16S ribosomal RNA, and cytochrome b gene PCR products. Similarly, mosquito arbovirus infections were identified by HRM analysis and sequencing of Alphavirus- and Flavivirus-specific RT-PCR products. Results: Of 2858 mosquitoes collected, 51 were engorged with blood meals from seven different vertebrate hosts, including humans, birds, domestic, and peridomestic animals and wildlife. Culex was the most abundant mosquito genus, with Culex pipiens being the most abundant species in both study regions. Among MMNR samples, we detected dengue serotype-2 virus (DENV-2) for the first time in Aedes tarsalis and Aedes tricholabis, as well as Sindbis virus in male Cx. pipiens. We also detected DENV-2 in Aedes aegypti sampled from locations near the SHNR. Human and diverse wildlife blood meals were identified, including bushbuck blood in the dengue-infected Ae. tarsalis and both human and hippopotamus blood in a single Eretmapodites chrysogaster mosquito. Conclusions: Our findings highlight the potential risk of sylvatic dengue and Sindbis transmission to humans by zoophilic mosquitoes at human-wildlife interfaces in Africa. Of specific importance, we provide evidence of sylvatic DENV-2 in Ae. tarsalis and Ae. tricholabis, representing potential new dengue vectors.